'More Product, Less Process' (MPLP): An early printed book project. (September 2022) - Attar, Karen
This article addresses the challenge to make printed hidden collections known quickly without sacrificing ultimate quality. It takes as its starting point the archival mantra 'More product, less process' and explores its application to printed books, mindful of projects in the United States to catalogue 19th- and 20th-century printed books quickly and cheaply with the help of OCLC. A problem is lack of time or managerial inclination ever to return to 'quick and dirty' imports. This article is a case study concerning a collection of 18th-century English imprints, the Graveley Parish Library, at Senate House Library, University of London. Faced with the need to provide metadata as quickly as possible for digitisation purposes, Senate House Library decided, in contrast to its normal treatment of early printed books, to download records from the English Short Title Catalogue and amend them only very minimally before releasing them for public view, and to do this work from catalogue cards rather than the books themselves. The article describes the Graveley Parish collection, the project method's rationale, and the advantages and disadvantages of sourcing the English Short Title Catalogue for metadata. It discusses the drawbacks of retrospective conversion (cataloguing from cards, not books): insufficient detail in some cases to identify the relevant book, and ignorance of the copy-specific elements of books which can constitute the main research interest. The method is compared against cataloguing similar books from photocopies of title pages, and retrospective conversion using English Short Title Catalogue is compared against retrospective conversion of early printed Continental books from cards using Library Hub Discover or OCLC. The control groups show our method's effectiveness. The project succeeded by producing records fast that fulfilled their immediate purpose and simultaneously would obviously require revisiting. The uniform nature of the collection enabled the saving of time through global changes.